New Movements - "Thomson, Alan Craft" (London)
"""Published in association with the United Society for Christian Literature for the Theological Education Fund."" Includes bibliographical references (p. xiii) and index."
Keywords: CHURCH HISTORY - PRIMITIVE AND EARLY CHURCH CA. 300-600-DICTIONARY